Le recours aux jeux vidéo dans la sensibilisation à la ville durable. Analyse comparative pour une évaluation en termes d’éthique et d’engagement du citoyen-joueur. - Hélène Bailleul; Anne Gagnebien (Netcom)
The article focuses on the interactions between sustainable cities and digital devices from the point of view of environmental citizenship. Focused on online games simulating the city of the future and its debate, the paper develops the issue of the player's commitment as a citizen. We particularly highlight the effects of digitalization and gamification of sustainable city debates citizenship. The mobilisation of a retrospective corpus - 4 online games published between 2006 and 2018 - makes it possible to show the progressive emergence of these game devices, the diversity of the actors who are behind them and the oscillation between the objective of environmental education and that of transmitting a positive message on environmental public action (political marketing). We observe both a certain standardisation of the subject and a gamification of ordinary political activity. Finally, the identification of the various forms of ethics mobilised by the player allows us to conclude on the impact of these devices on citizen engagement.